2018
DOI: 10.15419/bmrat.v5i12.508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prophylactic ketamine and pethidine to control postanesthetic shivering: A comparative study

Abstract: Background: Shivering is an undesirable complication following general anesthesia and spinal anesthesia, whose early control can reduce postoperative metabolic and respiratory complications. Therefore, this study aims to compare the effects of prophylactic injection of ketamine and pethidine on postoperative shivering. Methods: This double-blind clinical trial was performed on 105 patients with short-term orthopedic and ENT surgery. The patients were randomly divided into three groups; 20 minutes before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Ketamine probably regulates shivering by producing non-vibration-induced heat, acting on the hypothalamus and beta-adrenergic effects (10). Several studies have shown that ketamine is effective as a prophylactic drug for postoperative shivering (11)(12)(13)(14)(15)(16)(17). To reduce shivering, a dose of 0.5-0.75 mg/kg of ketamine is used, but this dose may lead to sedation, delirium, and hallucinations (6).…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine probably regulates shivering by producing non-vibration-induced heat, acting on the hypothalamus and beta-adrenergic effects (10). Several studies have shown that ketamine is effective as a prophylactic drug for postoperative shivering (11)(12)(13)(14)(15)(16)(17). To reduce shivering, a dose of 0.5-0.75 mg/kg of ketamine is used, but this dose may lead to sedation, delirium, and hallucinations (6).…”
Section: Introductionmentioning
confidence: 99%